2019
DOI: 10.1093/hmg/ddz077
|View full text |Cite
|
Sign up to set email alerts
|

The lysosomal disease caused by mutant VPS33A

Abstract: A rare lysosomal disease resembling a mucopolysaccharidosis with unusual systemic features, including renal disease and platelet dysfunction, caused by the defect in a conserved region of the VPS33A gene on human chromosome 12q24.31, occurs in Yakuts—a nomadic Turkic ethnic group of Southern Siberia. VPS33A is a core component of the class C core vacuole/endosome tethering (CORVET) and the homotypic fusion and protein sorting (HOPS) complexes, which have essential functions in the endocytic pathway. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(102 citation statements)
references
References 78 publications
20
82
0
Order By: Relevance
“…Currently, patients with mutations in HOPS core components VPS11, VPS16 and VPS33A have been reported in literature, which all show a neurodegenerative phenotype (11,(67)(68)(69)(70)(71)(72)(73)(74). Moreover, during our studies, a third patient with compound heterozygote mutations in VPS41 was identified (Personal communication by I. Stolte-Dijkstra, University Medical Center Groningen), bearing the VPS41 R662* mutation as well as a missense mutation (VPS41 H466R ), and displaying a similar neurological phenotype.…”
Section: Discussionmentioning
confidence: 61%
“…Currently, patients with mutations in HOPS core components VPS11, VPS16 and VPS33A have been reported in literature, which all show a neurodegenerative phenotype (11,(67)(68)(69)(70)(71)(72)(73)(74). Moreover, during our studies, a third patient with compound heterozygote mutations in VPS41 was identified (Personal communication by I. Stolte-Dijkstra, University Medical Center Groningen), bearing the VPS41 R662* mutation as well as a missense mutation (VPS41 H466R ), and displaying a similar neurological phenotype.…”
Section: Discussionmentioning
confidence: 61%
“…Most patients develop hematopoietic disorders including anemia, thrombocytopenia and leukocytopenia. An increase in serum IgM and decrease of IgG levels were found in MPSPS patients [49]. Bone marrow aspiration analysis showed hypoplastic bone marrow without any storage cells.…”
Section: Laboratory and Instrumental Examinationsmentioning
confidence: 87%
“…Examination of urine can reveal elevated levels of GAGs, specifically heparan and dermatan sulfate [4,5,49]. Accumulation of heparan sulfate was also detected in patient's plasma and skin fibroblasts.…”
Section: Gags and Enzymes Activitymentioning
confidence: 99%
See 2 more Smart Citations